Manuscript found in Accra [compact disc, unabridged] - Coelho, Paulo (Random House Audio, 2013)
Set in Jerusalem during the time of the Crusades. Christians, Arabs, and Jews have long lived together harmoniously. They are now being warned of an imminent attack and certain destruction; contemplating their demise, the community assembles to seek the counsel of a Greek Copt. The novel unfolds as a sequence of parables on love, faith, friendship, loyalty, and more.